?COORDINATION CHEMISTRY OF Zr(IV), Th(IV) AND U(VI) IONS CONTAINING 1,2 DIAMINOCYCLOHEXANE N N N' N' TETRA-ACETIC ACID (DCTA) AND SOME MONODENTATE ORGANIC LIGANDS (Biological Sciences - PJSIR, 1995)
Some new mixed ligand complexesof zirconium (IV)containing 1,2diarninocyclohexane NNN' N' tetra-acetic acid (DCTA) andsome monodentatc organic ligands havebeensynthesizedandcharacterized. Complexes of thorium (IV) and uranium (VI) containing OCTA only have also been reported here. OCTA behaves as a hexadentate, quadrinegative ligand in all the zirconium, thorium and uranium complexes. Zirconium and uranium complexes are presumably seven and eight-coordinated respectively whereas thorium complex is octahedral. The complexes have thecompositions: [Zr(OCTA)L}.nHp (wheren= 1,2 and3;L=pyridine-J-oxide, triphenylphosphine oxide (Ph.Pff), triphenylarsine oxide (Ph)AsO), pyridine and aniline), [Th(OCTA)].2HP and H2[UOiDCTA)].Hp.